Sistema perimetral firewall y fortalecimiento de la seguridad en el data center de la ESPAM MFL - Delgado Zambrano, Pablo Ricardo (2017)
With the objective of improving information security in the Data Center of the Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, a perimeter firewall software was implemented based on free code and mounted on a virtual server. For this, the collection of information was made using tools such as surveys, observation sheets and interviews. In addition, three firewall security systems were chosen and a comparative study applied with the checklist tool determined the software that was used, in this case Pfsense. Then the system was installed on the VMWARE platform for the virtualization of the firewall, and consequently to the configuration of the rules and levels of security of the firewall. With the implementation of the firewall server, results were obtained in terms of improving data protection and security in the network, facilitating the control, blocking and monitoring of computer attacks to the internal network of the university, which contributed Cost reduction and management of new plans at Data Center security levels in less time.